2011
DOI: 10.3390/pharmaceutics3040793
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of Natural Polyphenolic Compounds; a Review

Abstract: Natural polyphenols are valuable compounds possessing scavenging properties towards radical oxygen species, and complexing properties towards proteins. These abilities make polyphenols interesting for the treatment of various diseases like inflammation or cancer, but also for anti-ageing purposes in cosmetic formulations, or for nutraceutical applications. Unfortunately, these properties are also responsible for a lack in long-term stability, making these natural compounds very sensitive to light and heat. Mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
424
0
17

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 695 publications
(445 citation statements)
references
References 131 publications
4
424
0
17
Order By: Relevance
“…The FT-IR spectra obtained after addition of GSE-OPC during crosslinking stage showed similar pattern to GSE-OPC spectra, indicated that GSE-OPC had coated the cooled capsules droplet of Chitosan-Gelatin (B). This result aligned with [37] which explained that if the oligomers of polyphenol are insoluble in the droplets (which refer to capsules); a membrane is formed around them thus encapsulating the droplet. The polyphenolic compound constitutes the droplet, and the crosslinking reaction stabilizes the molecule which was proven by establishment of ester bonds detected from infrared spectroscopy.…”
Section: Ft-ir Spectrasupporting
confidence: 83%
“…The FT-IR spectra obtained after addition of GSE-OPC during crosslinking stage showed similar pattern to GSE-OPC spectra, indicated that GSE-OPC had coated the cooled capsules droplet of Chitosan-Gelatin (B). This result aligned with [37] which explained that if the oligomers of polyphenol are insoluble in the droplets (which refer to capsules); a membrane is formed around them thus encapsulating the droplet. The polyphenolic compound constitutes the droplet, and the crosslinking reaction stabilizes the molecule which was proven by establishment of ester bonds detected from infrared spectroscopy.…”
Section: Ft-ir Spectrasupporting
confidence: 83%
“…Crude extracts from plants with a history of use in folk medicine have been screened in vitro for antibacterial activity (5). Some researchers have reported synergistic eff ect of naturally occurring fl avonoids and other antibacterial agents against resistant strains of bacteria (8,9). Due to the problem of microbial resistance to antibiotics, att ention is given to biologically active components isolated from plant species commonly used in herbal medicine, as they can be used as antimicrobial preparations (10)(11)(12).…”
Section: Effect Of Encapsulation On Antimicrobial Activity Of Herbal mentioning
confidence: 99%
“…Despite having valuable health benefits, bioavailability and clinical efficacy of FA remain substantially limited owing to its lower solubility and permeability in aqueous medium as compared to other solvents such as ethanol, acetone and dimethylsulphoxide (Munin and Lévy 2011;Soobrattee et al 2005). Attempts have been made to increase its solubility and bioavailability through encapsulation in biodegradable polymeric nanoparticles (Vemula et al 2006;Salmaso et al 2007).…”
Section: Introductionmentioning
confidence: 99%